Principles of Correction of Colour Deficiency by Filter Glasses - Ábrahám, György (Periodica Polytechnica Mechanical Engineering, 2001)
With the aid of optimized filters we are able to shift thesensitivity curves of the L, M,S cones of the human eye along the wavelength axis.Since the shape of receptor sensitivity curve itself cannot be changed we apply a colourfilter in the path of the incoming light beam to modify the spectrum.This is equivalent to multiplying the receptor sensitivity function with thefilter transmission function.This method also reduces the sensitivity of the receptor but the selective colouradaptation mechanism of the eye can compensate this effect within a certain range.Using this method the maximum point of the sensitivity curve can be shifted to thedesired direction.This method can be used to improve the colour vision of anomalous trichromateswith shifted sensitivity curves and also to enhance the colour discrimination of thenormal eye optimized for a specified task.